Celiac Disease in Different Age Groups and Gender in Pakistan - Jamila , Rizwan Ahmed Kiani , Ishtiaq Ahmed , Jehanzeb Khan Yousafzai , Wasif Mehmood ,Sajjad Ahmed Khan , Waqas Ahmad , Muhammad Kamran (Journal of Rawalpindi Medical College, 2018)
Background: To examine the gender and age distribution of individuals with celiac disease (CD). Methods: In this cross sectional study a total of 643 patients with suspicion of CD, belonging to all age groups and both genders were included. Blood sampling done for serologic screening, for tissue transglutaminase (TTG IgA,), Deaminated gliadenpeptide IgA (Anti gliaden IgA) and endomysial antibodies (EMA IgA).Tests were performed by ELISA based on principle of enzyme immunoassay. The quantitative data like age was measured as mean and categorical data like sex, age categories, investigational findings and seasonal variables were analyzed as frequency and percentages. The association of age categories and gender of celiac disease patients was done using chi-square test. A p-value of < 0.05 was considered significant. Results: Age ranged from 1 to 81 years There was a male predominance. CD was more prevalent in the spring (33.4%) and summer (27.0%) seasons compared to autumn (23.6%) and winter (15.8%) seasons. Tissue Transglutaminase IgA was positive in 11.7% , with predominance in up to 15 years (17.0%), with least in 46-60 years (2.0%). Deaminated Gliadenopeptide IgA was positive in 24.1%. Highest number of positive patients seen in up to 15 years age (29.3%). Anti endomysial Abs were positive in 0.9%. The highest prevalence of CD (53.0%) was found in children and adolescents up to 15 years of age, whereas in older age categories it was less prevalent. Conclusion: Incidence of celiac disease in childhood is higher in our country. Adults are very less as compared to children. Male gender was predominantly affected.